The societal impact of electronic sport: a scoping review - Riatti, P.; Thiel, A. (German Journal of Exercise and Sport Research, 2022)
Competitive computer gaming, known as electronic sport or esport, is growing and professionalizing profoundly during the past years with experts struggling to allocate it in society. This scoping review explores existing evidence and identifies potential societal impact of esport by applying the Mapping Elite Sports Societal Impact Model. Main findings included insights on the motivation of passive and active esport consumption, beneficial socializing, pedagogical or educational aspects, hegemonial clinical pictures in esport, differing popularity regarding demographics and games, and potential interference of the esport economy in traditional sports. The findings implicate a paradigm shift in the world of sport. It can be stated that esport affects society in a positive and a negative way, although the fragmented body of research has only given superficial evidence so far. Future research needs to go into detail regarding the peculiarities and find approaches of isolating the positive aspects, while reducing the negative spin-offs and allow a well-regulated handling of esport on a broad societal level.